Surfactant Assisted Ball Milling: A Simple Top down Approach for the Synthesis of Controlled Structure Nanoparticle - Ali, Md. Eaqub; Ullah, Mahbub; Ma'amor, Azman; Hamid, Sharifah Bee Abd (Trans Tech Publications, 2013)
The unlimited applications of nanoparticles in human life are increasing day by day. Nanoparticles have drawn attention among researchers from academia to industry due to its large specific surface area, high chemical reactivity, physical affinity and interesting optical, electrical and magnetic properties. These properties of nanoparticles stimulate researchers to reduce particle sizes from few sub micrometers to nanometer levels. The successful application of nanoparticles depends on the simplicity of the methods for its cost effective synthesis. Since the very beginning of nanoscience, development of simple, low cost and high yielding methods has been a challenging task. Various approaches were proposed for the commercial production of nanomaterials from solid state. However, chemical method which is complicated and expensive showed limited success in the synthesis of controlled structure nanoparticles from rare-earth solid compounds. Among all the approaches, high energy ball milling with surfactant has been widely exploited for the synthesis of various nanomaterials, nanograins, nanocomposites from solid state. Self-assembled structures of surfactants provide a valuable tool for the controlled formation of nanostructure. In this process, the dispersion and enhanced grinding of particles are achieved in the reaction centers that reside in the microstructure of surfactants. In high-energy ball milling, plastic deformation, cold-welding and fracture are predominant factors which lead to a change in particle shape, size. These result in the formation of fine and dispersed particles. Stirred ball mill grinding is advantageous for nanoparticle production over other fine grinding techniques owing to its easy operation, simple construction, high size reduction rate and relatively low energy consumption. The aim of this systematic review is to represent the basic concept and applications of mechanical milling in the surfactant assisted synthesis of various nanomaterial, nanocomposite and nanocarbon materials.